Typology of agricultural productivity zones - Yu, Bingxin; Guo, Zhe (International Food Policy Research Institute, 2016)
The preceding chapter illustrated remarkable spatial heterogeneity in agricultural productivity across Africa at the system level, characterized by the inherent variations of climate, land suitability for agriculture, human and animal populations, expanding transportation networks, and other rural infrastructure. To help identify specific policies and investments to increase productivity in different locations, the analysis in Chapter 3 can be complemented by closer examination of the production agents within those systems. Within a given farming system, production agents also are heterogeneous, in terms of not only the resource constraints they face (Byerlee, Harrington, and Winkelmann 1982; Chambers and Jiggins 1987), but also how those resource constraints affect technology adoption and technological change that may result in productivity growth and possibly poverty reduction (Feder, Just, and Zilberman 1985; Feder and Umali 1993). The coevolution of these characteristics contributes to a dynamic context in which the nature and performance of agriculture manifest themselves through different spatial patterns of production portfolio and productivity. Identifying spatially common themes in these different portfolios can offer opportunities for developing and implementing strategies that cut across national boundaries and agroecological conditions.